Core@double-shells nanowires strategy for simultaneously improving dielectric constants and suppressing losses of poly(vinylidene fluoride) nanocomposites. (June 2018) - Yang, Minhao; Hu, Chaohe; Zhao, Hang; Haghi-Ashtiani, Paul; He, Delong; Yang, Yu; Yuan, Jinkai; Bai, Jinbo
Abstract: The core@double-shells structured TiO2 @Carbon@SiO2 nanowires (TiO2 @C@SiO2 NWs) with a uniform carbon inner shell and a SiO2 outer shell were successfully synthesized and subsequently incorporated into poly(vinylidene fluoride) (PVDF) matrix to prepare dielectric nanocomposites. Compared with the pristine TiO2 NWs/PVDF nanocomposites, the introduction of carbon interlayer as the inner shell between the TiO2 core and SiO2 outer shell offers the nanocomposites with two additional types of interfacial polarization, namely, (i) TiO2 /carbon and (ii) carbon/SiO2 interfacial polarizations. These additional interfacial polarizations promote the dielectric constants, and simultaneously the SiO2 insulating barrier layer suppresses the losses of the nanocomposites. Moreover, the nanocomposite with 30 wt % filler loading (19.78 vol %) exhibits an excellent dielectric performance with a constant of 41 and a loss tangent of 0.05 at 10 3 Hz. The multi-shells strategy reported here could be extended to a variety of inorganic hybrids to develop novel dielectric nanocomposites. Graphical abstract: Image 1